Blood glucose response and cellular changes associated with andrographolide treatment in insulin-resistant mice - Abdulameer, Hanaa Abdulabbas (2017)
The continual increase in the incidence of insulin resistance and its associated metabolic syndrome has necessitated the thrust for the development of therapeutic agents that could ameliorate this condition. It occurs when the normal circulating concentration of insulin fails to regulate the body glucose homeostasis. Insulin resistance has been common sequelae of obesity; insulin-resistant syndrome implies a series of abnormalities that frequently happen in insulin-resistant individuals. Available therapeutic agents and or medications to combat insulin resistance are not without several limitations including side effects. The need for a newer agent that could ameliorate insulin resistance with minimal or no side effect is therefore a global necessity Although the use of andrographolide for therapeutic purposes has gained wide acceptability, it's usage in the treatment of prediabetic or insulin resistance condition that is associated with type 2 diabetes has not been evaluated. Moreover, the studies about the effect of andrographolide on insulin resistance still few and no study demonstrated the effect of andrographolide on ultrastructural changes that related with insulin resistance disorder. This study was undertaken to investigate pure on the andrographolide potential to ameliorate impaired glucose tolerance and insulin resistance in high fat diet male mice. The mice were fed with high-fat diet (45% dietary energy from fat) for 24 weeks to induce insulin resistance. Upon confirmation of insulin resistance, these mice were then divided into four groups of 12 mice each. The control negative group (CN) received normal chow and three high-fat diet groups, which were; control positive group HPD (CP), high-fat diet group with andrographolide at 25 mg/kg (HPA25), and high-fat diet with andrographolide at 50 mglkg (HFA50).Alternatively, the results in present study are illustrated after 15 days treatment with andrographolide. Andrographolide treatment groups (HFA2S, HFASO) had significantly (P<O.05) reduced the body weight, fasting serum glucose levels, intraperitoneal glucose tolerance test (IPGTT) and intraperitoneal insulin tolerance test (IPITT). Also we determined the effect of andrographolide significant (P<O.05) reduced on the corresponding area under the curve of glucose (AVCg), the area under the curve of insulin (AVC), the insulin resistance index and HbA1C levels. Blood lipid profile tests, TAG, VLDL, gamma-glutamyl transferase GGT, liver enzymes (AST, ALT, ALP), leptin, resistin, oxidative stress malonaldehyde (MDA), kidney function tests (BUN, albumen, creatinine, total protein), pro-inflammatory cytokines (TNFa, IL-I~, IL-Ia, IL-6, MCP-Iand NF-KB), leptin, adiponectin and anti-oxidant activities (SOD, CAT, and GSH) were significantly reduced (P<O.05). In the CP group those tests quantified significant higher (p<O.05) before and post andrographolide treatment. In addition to that, blood glucose and insulin level were recorded significant decrease (P<O.05). On the other hand, there are detectable evident about ameliorative changes of andrographolide exerted on through histological sections, immunohistochemistry sections, ultrastructural examinations and gene expressions in the pancreas, liver, skeletal muscle, adipose tissue and kidney of treated male mice. Results showed the HFA50 group had the greatest histological, immunohistochemical, ultrastructural and gene expressions significant (p<O.05) reduced changes on regeneration cell injuries, reduced inflammation, macrophage cell infiltrations of pancreatic cells, liver, adipose, and kidney. Whereas, the HFA25 group showed significant (p<O.05) least decrease in histological, immunohistochemical, ultrastructural and gene expressions changes that include regeneration of cell injuries, reduced inflammation, and macrophage cell infiltrations of pancreatic cells, liver, adipose and kidney. Importantly, this result were attended with a significant (p<O.05) tissues healing sings (increased in some and large size rough endoplasmic reticulum, increased secretory granules of pancreas tissue and increased the number of mitochondria in the HFA50 group and least extent the HFA2Sgroup compared to the CP group. Furthermore, we observed a significant differences (p<O.05) in some gene expressions between treated groups. The HFA50 appeared significant (p<O.05) down-regulation of cytokines and interleukins genes expressions (TNFa, IL-I~, ILIa, IL-6, MCP-I and NF-KB). In contrast, up regulation of GLUT4, GLUT I, PPARa, PPARy and SREBPs genes expressions. While, the HFA25 appeared least gene expressions changes compared to the CP group. Overall, our results concluded that the anti-insulin resistance effect seen in andrographolide treatment is associated with restoration of insulin sensitivity and alleviated pathological changes in the pancreas, liver, adipose and kidney tissues. It is possible that andrographolide has potential capability to direct cellular regeneration through anti-pro-inflammatory cytokines inhibition and increase glucose transporter gene expressions at the cellular levels.